THE EFFECTS OF VİSUAL WARNİNGS ON CİGARETTE PACKAGİNG (Third Sector Social Economic Review, 2013)
The utilization of verbal and graphical warnings on cigarette packages is obligated in Canada and many other countries in 2001. That regulation is accepted in 2008 in Turkey. However, warnings on cigarette packages differ among countries. That difference is related to intensity of aroused fear and perceived threat. Researches on fear appeal show that there is a positive linear relationship between message acceptance and fear-arousing conditions. Nevertheless, intensity degree of the threat in fear appeal causes ethical arguments. Although many researches have been done, there is still no consensus on what intensity of aroused fear is the most effective.The aim of this research is to explain mental evaluation processes of cigarette warnings in consumer minds. According to that, fear appeal theory, models and researches indexed in SSCI or SCI (Social Science Citiation Index/ Science Citiation Index) are discussed.
Keywords: Cigarette warnings; fear appeal; cognitive responses; affective responses